Entrepreneurship : The Practice and Mindset - Neck, Heidi M. (SAGE Publications, Inc. (US), 2023)
Recipient of a 2021 Textbook Excellence Award from the Textbook & Academic Authors Association (TAA) Entrepreneurship: The Practice and Mindset emphasizes practice and learning through action, helping students adopt an entrepreneurial mindset so they can create opportunities and take action in uncertain environments. Based on the world-renowned Babson Entrepreneurship program, the updated Third Edition aids in the development of the entrepreneurial skillset and toolset that can be applied to startups as well as organizations of all kinds. Whether your students have backgrounds in business, liberal arts, engineering, or the sciences, this text will take them on a transformative journey and teach them crucial life skills. This title is accompanied by a complete teaching and learning package. Contact your Sage representative to request a demo. Learning Platform / Courseware Sage Vantage is an intuitive learning platform that integrates quality Sage textbook content with assignable multimedia activities and auto-graded assessments to drive student engagement and ensure accountability. Unparalleled in its ease of use and built for dynamic teaching and learning, Vantage offers customizable LMS integration and best-in-class support. It′s a learning platform you, and your students, will actually love. Learn more. Assignable Video with Assessment Assignable video (available in Sage Vantage) is tied to learning objectives and curated exclusively for this text to bring concepts to life. Watch a sample video now. LMS Cartridge: Import this title’s instructor resources into your school’s learning management system (LMS) and save time. Don’t use an LMS? You can still access all of the same online resources for this title via the password-protected Instructor Resource Site. Learn more.